Circadian control of human cardiovascular function. (April 2021) - Thosar, Saurabh S.; Shea, Steven A.
Abstract: Endogenous circadian rhythms prepare the cardiovascular (CV) system for optimal function to match the daily anticipated behavioral and environmental cycles, including variable activities when awake during the day and recuperation when sleeping at night. The overall day-night patterns in most CV variables result from the summation of predictable circadian effects with variable behavioral and environmental effects on the CV system. The circadian system has also been implicated in the morning peak in the incidence of adverse CV events, including myocardial infarction, stroke, and sudden cardiac death. We discuss the resting and stress-reactive circadian control of CV physiology in humans and suggest future research opportunities, including improving CV therapy by optimally timing therapy relative to a person's internal body clock time. Highlights: The suprachiasmatic nuclei are the seat of the central circadian clock. Peripheral circadian clocks exist throughout the cardiovascular (CV) system. Together, these clocks orchestrate resting and responsive rhythms in CV physiology. Day-night CV patterns result from the summation of circadian and behavioral effects. Timing drugs to specific circadian phases is a new opportunity to optimize therapy.